High‐Resolution Records of Millennial‐Scale East Asian Winter Monsoon in the Shelf Sea of Eastern China. Issue 7 (31st March 2023) - Shi, Yong; Xu, Xiaomei; Yang, Guang; Du, Jiabi; Lv, Jixuan; Zhang, Shuo; Liu, Shengjing; Liu, Tao; Zhang, Zhenyu; Gao, Shu; Gao, Jianhua
Abstract: The evolution of the East Asian winter monsoon (EAWM) during the Holocene remains controversial because of the lack of reliable proxies. In this study, a link between cross‐front transport and the EAWM was found in the North Yellow Sea, and the EAWM intensity could be imprinted in the leaked sediment, which permits reliable reconstruction of the EAWM on well‐preserved offshore deposition. By comparison with instrumental data, the wind speed of the EAWM since 4.4 ka was quantitatively reconstructed for the first time at high resolution (∼5 yr). The results show that the EAWM gradually weakened in the mid‐to‐late Holocene, which was likely controlled by solar insolation, and that there has been a negative relationship between the EAWM and temperature on the centennial scale since ∼2.0 ka; this relationship was reversed by increasing CO2 emissions during the Current Warm Period. Plain Language Summary: The East Asian monsoon is characterized by a distinct seasonal reversal of monsoon flow driven by temperature differences between the Pacific Ocean and the East Asian continent. It influences more than 2 billion people around East Asia by regulating the risk of drought or flooding. However, the evolution of the East Asian winter monsoon (EAWM) in the mid‐to‐late Holocene remains elusive, limiting our understanding of its driving force and projections under climate change. This study analyzed sediment transport dynamics under varying winter monsoons in the North Yellow Sea. It was found that coastal sediments could be transported offshore, and their pathways differed under different strengths of the winter monsoon. Based on the sedimentary records of offshore muddy deposition, the EAWM proxy was extracted, and the wind speed of the EAWM from 4.4 ka was quantitatively reconstructed. A gradual weakening trend during 4.4–0.7 ka and a dramatic strengthening after 0.2 ka were found in the EAWM; the EAWM was negatively related to the temperature on the centennial scale since ∼2.0 ka, but this relationship was reversed by an increase in CO2 emissions since ∼1800 CE, indicating a shift in the controlling mechanism. Key Points: A link between cross‐front transport and the East Asian winter monsoon (EAWM) was found in the shelf sea, and the leaked sediment was used to reconstruct the EAWM The wind speed of the EAWM since 4.4 ka was quantitatively reconstructed at high resolution (∼5 yr) for the first time Correlation between the EAWM and the temperature on the centennial scale since ∼2.0 ka was reversed by the increasing CO2 at the Current Warm Period